UNWAR Tingkatkan Bahasa Inggris Surat-Menyurat Karyawan Hotel Sthala Ubud - Made Susini; Nyoman Sujaya; Ni Ketut Sukiani; Made Detrichyeni (Postgraduated Community Service Journal, 2024)
This article deals with Community Service with the scheme Community-Based Empowerment conducted by the service team from Faculty of letters Warmadewa University. The service partner was the staff of Sthala hotel, Ubud Bali. The focus of this community service was about English language training for correspondence. The method applied includes observation, identifying problem, lectures, mentoring, discussions and evaluation. After the service was carried out, it could be explained that the community service could run well. The staff of the hotel have been able to understand what correspondence is. They have been able to improve their skills in English grammar. Partners are also able to use formal English in correspondence. Partners have also been able to implement the 7 Cs: real, concise, concrete, correct, coherent, complete, and courteous in writing formal letters.